2015
DOI: 10.1002/chem.201502572
|View full text |Cite
|
Sign up to set email alerts
|

Iridium(III) Photocatalysis: A Visible‐Light‐Induced Dearomatizative Tandem [4+2] Cyclization to Furnish Benzindolizidines

Abstract: A photocatalytic dearomatizative tandem [4+2] cyclization between N-(2-iodoethyl)indoles and a variety of alkenes leads to tri- and tetracyclic benzindolizidines with high diastereoselectivity and yield. The intermolecular annulation reaction is performed under visible-light irradiation and employs [Ir(ppy)3] or [Ir(dtbbpy)(ppy)2] PF6 as photocatalysts, in combination with tertiary amines as electron and hydrogen atom donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 62 publications
0
20
0
1
Order By: Relevance
“…Indole substrates 3 bearing C-3 acceptor substituents (R = CO 2 R, COR, CN) efficiently underwent dearomatization under our reaction conditions, and products 5 were obtained with excellent diastereoselectivity. [5] Our results in the tandem (4+2) cyclizations of substrates 3 with alkenes 4 conditions. A combined experimental and computational study revealed that only very subtle structural changes in the substrate-reactant complexes of the key radical intermediates with amine radical cations steer the divergent product selectivities, instead of the usual reactivity parameters such as ionization potentials or partial charges.…”
Section: +mentioning
confidence: 76%
See 4 more Smart Citations
“…Indole substrates 3 bearing C-3 acceptor substituents (R = CO 2 R, COR, CN) efficiently underwent dearomatization under our reaction conditions, and products 5 were obtained with excellent diastereoselectivity. [5] Our results in the tandem (4+2) cyclizations of substrates 3 with alkenes 4 conditions. A combined experimental and computational study revealed that only very subtle structural changes in the substrate-reactant complexes of the key radical intermediates with amine radical cations steer the divergent product selectivities, instead of the usual reactivity parameters such as ionization potentials or partial charges.…”
Section: +mentioning
confidence: 76%
“…[5] The reductive quench of the electronically excited photocatalyst by the amine generates an amine radical cation 11 and the monoreduced catalyst [PC] -to reduce iodide 3. The resulting primary carbon radical undergoes 1,4-addition with the alkene 4 followed by intramolecular 6-exo-trig ring closure.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations